Pengaruh Pengawasan .danPemberdayaan terhadapPerilaku Karyawan Dalam Pelayanan Perijinan Pada Dinas Perindustrian dan Perdagangan Kota Medan - Sitorus, Monang (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2004)
The objective research and analysis influence controlling and empowering to employees behavior in serivice permit in board of industry and trade to Board of Industry and Trade of Medan City. The grand theory controlling testing writer by Robbins and Coulter (2005), empowering testing writer by Clutterbuck dan Kernaghan (2003) and theory employees behavior testing writer by Mar'at (1981). The use of methodology eksplanatori survey and all responden is sensus. The data were analyzed by using Path Analysis. The infuence the controlling (X1) to employees behavior (Y) indirect and direct is 23.8%; lnfuence empowering (X2) to employees behavior (Y) is 15.9%. The effect controlling (X1) and empowering (X2) to employees behavior (Y) is 39. 7%, and the residue 60. 3% influenced the other dissimilar factor (epsilon).